Meta-analysis of stent-assisted coiling versus coiling-only for the treatment of intracranial aneurysms. (September 2016) - Phan, Kevin; Huo, Ya R.; Jia, Fangzhi; Phan, Steven; Rao, Prashanth J.; Mobbs, Ralph J.; Mortimer, Alex M.
Highlights: Fourteen observation studies regarding stent-assisted coiling versus coiling-only for intracranial aneurysms were pooled. There was a similar rate of immediate occlusion. Progressive thrombosis was higher in stent-assisted coiling. Aneurysm recurrence was lower in stent-assisted coiling. Mortality was higher for stent-assisted group. Abstract: Endovascular coil embolization is a widely accepted and useful treatment modality for intracranial aneurysms. However, the principal limitation of this technique is the high aneurysm recurrence. The adjunct use of stents for coil embolization procedures has revolutionized the field of endovascular aneurysm management, however its safety and efficacy remains unclear. Two independent reviewers searched six databases from inception to July 2015 for trials that reported outcomes according to those who received stent-assisted coiling versus coiling-only (no stent-assistance). There were 14 observational studies involving 2698 stent-assisted coiling and 29, 388 coiling-only patients. The pooled immediate occlusion rate for stent-assisted coiling was 57.7% (range: 20.2%–89.2%) and 48.7% (range: 31.7%–89.2%) for coiling-only, with no significant difference between the two (odds ratio [OR} = 1.01; 95% confidence intervals [CI}: 0.68–1.49). However, progressive thrombosis was significantly more likely in stent-assisted coiling (29.9%) compared to coiling-only (17.5%) (OR = 2.71; 95% CI: 1.95–3.75). Aneurysm recurrence was significantly lower in stent-assisted coiling (12.7%) compared to coiling-only (27.9%) (OR = 0.43; 95% CI: 0.28–0.66). In terms of complications, there was no significant difference between the two techniques for all-complications, permanent complications or thrombotic complications. Mortality was significantly higher in the stent-assisted group 1.4% (range: 0%–27.5%) compared to the coiling-only group 0.2% (range: 0%–19.7%) (OR = 2.16; 95% CI: 1.33–3.52). Based on limited evidence, stent-assisted coiling shows similar immediate occlusion rates, improved progressive thrombosis and decreased aneurysm recurrence compared to coiling-only, but is associated with a higher mortality rate. Future randomized controlled trials are warranted to clarify the safety of stent-associated coiling.